2018
DOI: 10.1371/journal.pone.0196097
|View full text |Cite
|
Sign up to set email alerts
|

Benthic macrofauna bioturbation and early colonization in newly flooded coastal habitats

Abstract: How will coastal soils in areas newly flooded with seawater function as habitat for benthic marine organisms? This research question is highly relevant as global sea level rise and coastal realignment will cause flooding of soils and form new marine habitats. In this study, we tested experimentally the capacity of common marine polychaetes, Marenzelleria viridis, Nereis (Hediste) diversicolor and Scoloplos armiger to colonize and modify the biogeochemistry of the newly established Gyldensteen Coastal Lagoon, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 72 publications
(109 reference statements)
1
9
0
1
Order By: Relevance
“…This artifact may explain the relatively high DIN and DIP fluxes observed from 2015 to 2019 compared to the soil loss and model calculations (Table 4). The initial first year rates of in situ DIN and DIP release from flooded soil to overlying water observed in the present study are comparable to those reported by Valdemarsen et al (2018) right after experimental flooding of darkened Gyldensteen soils.…”
Section: N and P Exchange Patterns And The Underlying Mechanismssupporting
confidence: 90%
“…This artifact may explain the relatively high DIN and DIP fluxes observed from 2015 to 2019 compared to the soil loss and model calculations (Table 4). The initial first year rates of in situ DIN and DIP release from flooded soil to overlying water observed in the present study are comparable to those reported by Valdemarsen et al (2018) right after experimental flooding of darkened Gyldensteen soils.…”
Section: N and P Exchange Patterns And The Underlying Mechanismssupporting
confidence: 90%
“…Descriptions of ecosystem engineering have a particular relevance in predicting changes in landscape evolution (Pearce, 2011). Process-based models of bioturbation effects as those we presented may contribute to the prediction of both long and short-term morphodynamic trends (Hu, et al, 2015;Hu, et al, 2018) also as response to human modifications of coastal landscapes (Cozzoli, et al, 2017;Valdemarsen, et al, 2018). Having such a metabolismbased relationship does enable extrapolations on how change in benthic community metabolism may influence bioturbation effects on sediment resuspension.…”
Section: Accepted Manuscript Application Potentialmentioning
confidence: 99%
“…These bioturbations may greatly affect biochemical processes, ecosystem functioning, and microbial activities in such sediments, due to modifi cations in the exchange rates of oxygen, carbon dioxide, and nutrients between the sediment and the overlying water. 83 During this research, habitats characterised by the presence of bioturbations were documented in four of the seven surveyed areas: Eolo seamount, North of Lipari, Secca dei Piesci and Stromboli. The species observed to form these bioturbations were Cepola macrophthalma, Goneplax rhomboides, Lesueurigobius spp.…”
Section: Soft Bottoms With Bioturbationsmentioning
confidence: 99%